Impact of Cancer Localization on Symptom Burden and Quality of Life in Head and Neck Cancers: A Comparative Study - Balk, Matthias; Rak, Atina; Rupp, Robin; Sievert, Matti; Müller-Hübner, Sarina Katrin Ursel; Koch, Michael; Iro, Heinrich; Gostian, Magdalena; Putz, Florian; Weissmann, Thomas; Allner, Moritz; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Background: Head and neck cancer (HNC) is a critical concern in oncology, with notable disparities in survival rates. While the long-term symptom burden in HNC survivors and its impact on quality of life (QoL) has been explored, there is limited understanding of the influence of cancer localizations on these aspects. This study aims to elucidate the role of cancer localizations in shaping long-term outcomes in HNC patients. Methods: A cross-sectional study was conducted at the University Hospital Erlangen’s Department of Otolaryngology, exploring the impact of cancer localization on symptom burden and QoL in 138 HNC patients using the University of Washington Quality of Life Questionnaire Version 4. Results: In our study of HNC patients, we investigated symptom burden across different cancer localizations, including oral cavity, oropharyngeal, hypopharyngeal, laryngeal, and cancer of unknown primary (CUP). While we found no significant variations in parameters such as pain, appearance, and activity, notable differences emerged in swallowing, speech, and salivation. Patients with oral cavity and laryngeal carcinomas had significantly higher swallowing and salivation scores compared to those with oropharyngeal carcinoma and CUP, while speech-related symptoms were lower for oral cavity and laryngeal carcinoma patients. Importantly, these symptom differences did not significantly impact health-related and overall QoL. These findings emphasize the nuanced interplay between symptomatology and QoL in different HNC cancer localizations. Conclusion: The research highlights significant disparities in post-treatment symptoms across different HNC localizations and underscores the need for personalized treatment and management strategies to address unique challenges associated with each HNC type, ultimately aiming to enhance post-treatment QoL.
CRIS-Team Scopus Importer:2024-11-08
Keywords: advanced-stage cancer; cancer; disease stage; early-stage cancer; follow-up; head and neck cancer; individualized care; patient-reported outcome; physical symptoms; psychological symptoms; quality of life; survivorship; symptom burden